Assessingthe Kinesiophobia and Depression Status at Return to Sport Following Sport Related Injuries in Contact and Non-Contact Sports - Kaçoğlu, Celil; Atalay, Erdem; Turhan, Begümhan (My University, 2018)
Objective: The aim of this study is to examine the levels of kinesophobia and depressionfollowing sports injuries in physically contact and non-contact sports.Material and Methods: A total of 130 male athletes from 14 different sports, who wereinjured at least six months before were included in the study. Individuals participating in thestudy were interviewed by means of the Beck Depression Inventory and the TampaKinesiophobia Scale. Participants were also asked to complete a form to determine theinjuries they had experienced.Results: There were no statistically significant differences between the physically contactand non-contact sport groups’ kinesiophobia and depression scores (p0.05). There wasno significant correlation between these two scores (r0.27, p0.05). Beck DepressionInventory scores following injuries that occurred in training and competition weresignificantly higher in physically contact sports than non-contact sports (p0.05 andp0.001, respectively).Conclusion: Depression and kinesophobia scores following sport injuries were notsignificantly different for physically contact and non-contact sports. Kinesophobia is notrelated to the emotional status of athletes.

Amaç: Bu çalışmanın amacı fiziksel temas içeren ve içermeyen sporlarda sporyaralanmasını izleyen süreçte kinezyofobi ve depresyon düzeylerini incelemektir.Gereç ve Yöntem: Bu çalışmaya en az altı ay önce spor yaralanması geçirmiş 130 erkeksporcu dâhil edildi. Çalışmaya katılan sporcular, bire bir görüşme şeklinde Beck DepresyonEnvanteri ve Tampa Kinezyofobi Ölçeği ile değerlendirildi. Ayrıca katılımcılardan geçirmişoldukları yaralanmaya ilişkin bilgileri değerlendiren bir form doldurmaları istendi.Bulgular: Fiziksel temas içeren ve fiziksel temas içermeyen sporlar arasında kinezyofobive depresyon skorları istatistiksel olarak anlamlı düzeyde farklılık göstermemektedir(p0.05). Depresyon skorları ile kinezyofobi skorları arasında korelasyon bulunmadı(r0.27). Antrenman ve müsabaka sırasında meydana gelen yaralanmalardan sonrabelirlenen depresyon skorlarının fiziksel temas içeren sporlarda, fiziksel temas içermeyen sporlara göre anlamlı oranda yüksek olduğu bulundu (sırasıylap0.05 ve p0.001).Sonuçlar: Spor yaralanmaları sonrası depresyon ve kinezyofobi skorlarının fiziksel temas içeren ve içermeyen sporlararasında farklı olmadığı belirlendi. Kinezyofobinin sporcuların duygusal durumlarıyla ilişkili olmadığı söylenebilir.
Fiziksel Temas İçeren ve İçermeyen Sporlarda Yaralanma Sonrası Spora Dönüşte Kinezyofobi ve Depresyon Düzeylerinin İncelenmesi
Keywords: Eğitim; Eğitim Araştırmaları; Spor Bilimleri